Histological analysis of the medial gastrocnemius muscle in young healthy children - Andries, Anke; Deschrevel, Jorieke; Maes, Karen; De Beukelaer, Nathalie; Corvelyn, Marlies; Staut, Lauraine; De Houwer, Hannah; Costamagna, Domiziana; Nijs, Stefaan; Metsemakers, Willem-Jan; Nijs, Elga; Hens, Greet; et al. (Frontiers in Physiology, 2024)
Introduction: Histological data on muscle fiber size and proportion in (very) young typically developing (TD) children is not well documented and data on capillarization and satellite cell content are also lacking. Aims: This study investigated the microscopic properties of the medial gastrocnemius muscle in growing TD children, grouped according to age and gender to provide normal reference values in healthy children. Methods: Microbiopsies of the medial gastrocnemius (MG) muscle were collected in 46 TD boys and girls aged 2–10 years subdivided into 4 age groups (2–4, 4–6, 6–8 and 8–10 years). Sections were immunostained to assess fiber type cross-sectional area (fCSA) and proportion, the number of satellite cells (SC), capillary to fiber ratio (C/F), capillary density for type I and II fiber (CFD), capillary domain, capillary-to-fiber perimeter exchange index (CFPE) and heterogeneity index. fCSA was normalized to fibula length2 and the coefficient of variation (CV) was calculated to reflect fCSA intrasubject variability. Results: Absolute fCSA of all fibers increased with age (r = 0.72, p < 0.001) but more in boys (+112%, p < 0.05) than in girls (+48%, p > 0.05) Normalized fCSA, CV and fiber proportion did not differ between age groups and gender. C/F was strongly correlated with age in boys (r = 0.83, p < 0.001), and to a lesser extent in girls (r = 0.37, p = 0.115), while other capillary parameters as well as the number of SC remained stable with increasing age in boys and girls. Discussion: This study provides reference values of histological measures in MG according to age in normally growing boys and girls. These data may be used as a reference to determine disease impact and efficacy of therapeutic approach on the muscle.